Food Safety Practices among Employees of Casual Dining Restaurants - Escario, Mary Grace (Journal of Interdisciplinary Perspectives, 2025)
Food handlers play a crucial role in ensuring food safety, as mishandling and negligence can lead to food contamination and the transmission of diseases. This study determined the food safety awareness and observance among employees of casual dining restaurants in Bacolod City, Negros Occidental in four key areas: food sourcing, preparation, handling, and storage. Utilizing a descriptive correlational research design, the study employed a questionnaire comprising 24 statements, each based on a 4-point Likert scale, to measure both the level of awareness and the extent of observance. A total of 19 casual dining restaurants participated, with consent from the relevant agencies secured prior to data collection. Convenience sampling was employed due to the fast-paced nature of the food service industry, yielding 422 employee respondents. The results revealed that most participants were aged 18-30, with 63% being male. The majority worked in operational roles such as front-of-house (42%) and kitchen staff (38%). Most participants (68%) had over two years of work experience. Findings indicated that participants rated their food safety awareness as "Very Aware”. Observance levels were rated as "Very Large Extent", demonstrating adherence to food safety. Significant differences were found in observance levels based on age and years of experience, indicating that older and more experienced employees presented better observance. A significant, positive relationship was also identified between awareness and observance. This means that the higher the level of awareness, the more likely food handlers observe food safety practices. The study recommends regular refresher training and collaboration with government agencies and academic institutions to enhance food safety practices further. Future researchers could conduct observational studies to validate these findings. They could also explore additional demographic factors and extend studies to other dining establishments.